1999
DOI: 10.1097/00003246-199911000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis and central venous catheter infections in critically ill patients: Results of a prospective study

Abstract: DC-related infections are associated with DC longevity. As shown by the 5-day-interval analysis, the incidence of DC-related infections did not increase with DC duration, suggesting that the risk for DC-related infections remained unchanged with time. The characteristics of DC-related infections in ICU patients were comparable to those previously reported for CVC-related infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
32
0
8

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 32 publications
11
32
0
8
Order By: Relevance
“…The higher mortality in this population may compete with catheterrelated bloodstream infection. In agreement with previous reports (17,19), the most frequently cultured microorganism was Staphylococcus epidermidis. Predominance of fungi may be, in part explained by greater broad-spectrum, predominantly antibacterial, antibiotic use in CRRT patients than IHD, as suggested by greater antimicrobial use noted in the Table 1.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The higher mortality in this population may compete with catheterrelated bloodstream infection. In agreement with previous reports (17,19), the most frequently cultured microorganism was Staphylococcus epidermidis. Predominance of fungi may be, in part explained by greater broad-spectrum, predominantly antibacterial, antibiotic use in CRRT patients than IHD, as suggested by greater antimicrobial use noted in the Table 1.…”
Section: Discussionsupporting
confidence: 93%
“…Of note, differences in the microbial findings could not be explained by anatomic site differences, since the mode of RRT served as a blocking variable in the jugular versus femoral randomization process (Table 1). Also, Gram positive bacteria were responsible for all catheter-related bloodstream infection, as previously reported (17).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The catheterization duration (7 days) reported in this study was similar to those reported in previous studies (5,8,(15)(16)(17)(18), ranging from 4.2 days (16) to 12.0 days (5). This short-term indwelling duration suggests that the extraluminal route of cathetertip colonization predominated (19).…”
Section: Discussionsupporting
confidence: 88%
“…The catheter duration was 7 days, in accordance with previous studies (22,29,30). The median indwelling time reported in this study is 2 days longer than the 5 days reported in the overall Cathedia cohort (7).…”
Section: Discussionsupporting
confidence: 65%